2018
DOI: 10.1021/acsomega.8b01255
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Multifunctional SrTiO3 Nanocatalyst Synthesized by Microwave and Oxalate Methods: Its Catalytic Application for Condensation, Hydrogenation, and Amination Reactions

Abstract: The present study deals with the synthesis of SrTiO 3 (STO) nanocatalysts by conventional oxalate and microwave-assisted hydrothermal methods. Thorough characterization of the nanocatalysts synthesized has been done by using various techniques such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy, N 2 physisorption, transmission electron microscopy, total acidity by pyridine adsorption method, and acidic strength by n -buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The corresponding SAED (selected area electron diffraction) pattern (see Figure (b)) shows the nanoparticles are well crystalline and the calculated (012), (004), and (211) plane corresponds to ZnTiO 3 , anatase TiO 2 , and rutile TiO 2 . Figure (c) shows the EDX (Energy dispersive X‐ray) spectra of the ZnTiO 3 @TiO 2 heterostructure nanomaterial, indicating the presence of Zn, Ti, and O only in the ZnTiO 3 @TiO 2 heterostructure nanomaterial …”
Section: Resultsmentioning
confidence: 99%
“…The corresponding SAED (selected area electron diffraction) pattern (see Figure (b)) shows the nanoparticles are well crystalline and the calculated (012), (004), and (211) plane corresponds to ZnTiO 3 , anatase TiO 2 , and rutile TiO 2 . Figure (c) shows the EDX (Energy dispersive X‐ray) spectra of the ZnTiO 3 @TiO 2 heterostructure nanomaterial, indicating the presence of Zn, Ti, and O only in the ZnTiO 3 @TiO 2 heterostructure nanomaterial …”
Section: Resultsmentioning
confidence: 99%
“…During the experiments, we observed that the colour of MB changed to light blue and eventually to a clear solution with degradation process. The decolourization of MB is not an indication of mineralization as it may be converted to a colourless substances [12,13]. The change in concentration of MB as a function of time in the presence of asprepared samples is shown in Fig.…”
Section: Fig1a Represents Xrd Pattern Of Single Phase Cubic Spinelmentioning
confidence: 99%
“…Potentiometric titrations have been used for characterizing the surface chemistry of different types of organic and inorganic NM with various FG, and have been applied to determine the number and nature of acidic sites (carboxy, lactone, phenol, and ester groups) on carbonbased materials like carbon dots (CD), nanocellulose/ nanobentonite composites, biochar particles, multi-walled carbon nanotubes, or cellulose nanocrystals [76][77][78][79][80], or to quantify hydroxy (silanol) and thiol groups on hybrid silica particles [81]. Potentiometric titrations have also been used to determine the total number of acidic sites on different catalyst materials like phosphotungstic acid-functionalized Sn-TiO 2 and organic-inorganic polyoxometalate NP, SrTiO 3 particles used to catalyze condensation, hydrogenation, and amination reactions, functionalized silica particles employed as catalysts for the esterification of linoleic acid, and photocatalytic TiO 2 / S-doped carbon hybrids [82][83][84][85][86]. For example, Wang et al potentiometrically quantified carboxy and amino groups on fluorescent CD prepared with different amounts of L-arginine or L-glycine (see Fig.…”
Section: Potentiometric Titrationmentioning
confidence: 99%